Critical choices : the United Nations, networks, and the future of global governance - Reinicke, Wolfgang H. (desLibris. Books collection., 2000)
The world that we live in today is changing dramatically. Economic and political liberalization, together with accelerating technological change, are driving the extraordinary process we know as ''globalization.'' This new global environment requires new approaches, new ideas, and innovative tools to address new challenges in areas as different as weapons control, climate change, genetic engineering, and labour standards. Critical Choices looks at one such tool: global public policy networks. In these networks, governments, international organizations, the corporate sector, and civil society j.